Naked conversations how blogs are changing the way businesses talk with customers - Scoble, Robert 1965-; Israel, Shel 1944- (Wiley, 2006)
Blogs offer businesses something that has long been lacking in their communication with customers: meaningful dialogue. Devoid of corporate-speak and empty promises, business blogs can humanize communication, bringing companies and their constituencies together in a way that improves both image and bottom line. Blogs are easily linked, allowing information to spread rapidly, and blog readers are active, not passive, participants in the communication. This book uses more than fifty case histories to explain why blogging is an efficient and infinitely more credible method of business communication. It explores how blogging has changed the rules of communication and competition, and gives business owners the tools to launch an effective blogging strategy--and the reasons why they should.--From publisher description.
Keywords: Blogues; Communication dans l'entreprise; Internet - Aspect social; Gesellschaft; Blogs; Business communication; Internet -- Social aspects; Kommunikation; Kundenbetreuung; Weblog